Regulation of aging and oxidative stress pathways in aged pancreatic islets using alpha-lipoic acid - Nobakht-Haghighi, Navid; Rahimifard, Mahban; Baeeri, Maryam; Rezvanfar, Mohammad Amin; Nodeh, Shermineh Moini; Haghi-Aminjan, Hamed; Abdollahi, Mohammad (Springer, 2018)
Oxidative stress has been involved in the aging process and the pathogenesis of type-2 diabetes, which is a serious health problem worldwide. This study investigates the anti-aging, anti-apoptotic, and antioxidant properties of alpha-lipoic acid (ALA), aiming to improve aged rat pancreatic cells. In this regard, half maximal effective concentration (EC50) of ALA based on the survival of aged pancreatic islet cells was determined as 100 mu M. Following this, p38 and p53 genes expression as key factors in aging, oxidative stress biomarkers, insulin secretion, and Pdx1 protein expression were evaluated using real-time PCR, ELISA reader, and fluorescence microscope. It was revealed that ALA reduces and controls the effects of aging on beta cells mainly by suppressing p38 and p53 at the gene level (P < 0.001 and P < 0.01), respectively, reducing reactive oxygen species (P < 0.001) and enhancing levels of thiols (P < 0.05) compared with the aged islets. Furthermore, both qualitative and quantitative investigations of insulin secretion have shown that ALA can improve aged cells' function and increase insulin secretion specially in the stimulating concentration of glucose. Also, the expression of Pdx1 was considerably increased by ALA in comparison to the aged pancreatic islets (P < 0.001). As far as the authors of the present study are concerned, this is the first study, which evaluated aging associated with p38 and p53 pathways, oxidative stress parameters, and the expression of insulin in beta cells of an aged rat and reaffirmed the fact that ALA has a significant antioxidant role in reducing the aging process.
Keywords: Senescence; Diabetes; Oxidative stress; Islet Cells; alpha-Lipoic acid